Evaluation of user‐interfaces for controlling movements of virtual minimally invasive surgical instruments. Issue 5 (5th May 2022) - Shabir, Dehlela; Anbatawi, Malek; Padhan, Jhasketan; Balakrishnan, Shidin; Al‐Ansari, Abdulla; Abinahed, Julien; Tsiamyrtzis, Panagiotis; Yaacoub, Elias; Mohammed, Amr; Deng, Zhigang; Navkar, Nikhil V.
Abstract: Background: Recent tele‐mentoring technologies for minimally invasive surgery (MIS) augments the operative field with movements of virtual surgical instruments as visual cues. The objective of this work is to assess different user‐interfaces that effectively transfer mentor's hand gestures to the movements of virtual surgical instruments. Methods: A user study was conducted to assess three different user‐interface devices (Oculus‐Rift, SpaceMouse, Touch Haptic device) under various scenarios. The devices were integrated with a MIS tele‐mentoring framework for control of both manual and robotic virtual surgical instruments. Results: The user study revealed that Oculus Rift is preferred during robotic scenarios, whereas the touch haptic device is more suitable during manual scenarios for tele‐mentoring. Conclusion: A user‐interface device in the form of a stylus controlled by fingers for pointing in 3D space is more suitable for manual MIS, whereas a user‐interface that can be moved and oriented easily in 3D space by wrist motion is more suitable for robotic MIS.